Preparedness Integration Education as an Effort to Improve Community Behavior in Facing Volcanic Eruption - Supardi Rustam; Sudirman Sudirman; Ta'adi Ta'adi (Universitas Padjadjaran, 2023)
Disaster preparedness is an important thing to accomplish. One way to improve preparedness behavior is through education. Preparedness Integration Education is an innovative educational method that integrates several methods and interactive media including the presentation of educational videos, focus group discussions (FGD) and simulations so that they become a series of disaster preparedness education procedures. The purpose of this activity is to improve community preparedness behavior in dealing with volcanic eruptions. This activity method is carried out in several stages including preparation, implementation and evaluation. The assessment instrument used a behavioral questionnaire that was guided by the five-parameter preparedness framework developed by LIPI in collaboration with UNESCO/ISDR in 2006. This activity was carried out using a nonequivalent pretest and posttest control group design involving 28 respondents from the community in each intervention group and control group who were taken using a non-probability sampling technique with the purposive sampling method. The intervention group was given preparedness integration education while the control group was given lecture method education. The data obtained were then analyzed using the Wilcoxon test and the Mann-Whitney test. This activity involved 28 respondents with an age range of 17-25 years. As for the evaluation of this activity, a quantitative analytic test was carried out with a non-equivalent one-group pretest and -posttest control group design with data on community behavior measurement in Dufa-dufa Village, North Ternate District. The evaluation results showed that people's behavior increased from 66.54% to 83.89% with p=0.000 after being given Preparedness Integration Education. Improved community behavior after being given Integrated Preparedness Education proves that disaster preparedness education that is oriented towards interactive media and sustainable methods where the educational information obtained can be directly practiced has a good influence on community preparedness behavior in dealing with volcanic eruptions. Based on these results it can be concluded that Preparedness Integration Education can improve community behavior regarding volcanic eruption preparedness. Keywords: Disaster, education, behavior.